Glacial and Sea Level History of Lowther and Griffith Islands, Northwest Territories: A Hint of Tectonics - Dyke, Arthur (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1993)
ABSTRACTLowther and Griffith islands, in the centre of Parry Channel, were overrun by the Laurentide Ice Sheet early in the last glaciation. Northeastward Laurentide ice flow persisted across at least Lowther Island until early Holocene déglaciation. Well constrained postglacial emergence curves for the islands confirm a southward dip of raised shorelines, contrary to the dip expected from the ice load configuration. This and previously reported incongruities may indicate regionally extensive tectonic complications of postglacial rebound aligned with major structural elements in the central Canadian Arctic Islands.